STRUCTURE OF THE AFAR AND TANZANIA PLUMES BASED ON THE REGIONAL TOMOGRAPHY USING ISC DATA - Koulakov I.Yu. (My University, 2007)
Establishment of the correlation between deep dynamics and processes observed at the daytime surface is an important fundamental problem of modern geodynamics. The study of mantle plumes, which are responsible for volcanic processes and riftogenesis in different parts of the Earth, occupies a special place in this problem. The system of rift depressions in East Africa and the Afar triple junction is the most striking example of the influence of mantle processes on the near-surface tectonic activity. The correlation between mantle dynamics and riftogenesis in this region has attracted the attention of many scholars around the world. Quantitative estimates of pull-apart forces in the lithosphere induced by an ascending plume. These works and a multitude of other observations demonstrate that rifting in East Africa is caused precisely by mantle processes.